2000
DOI: 10.1088/0266-5611/16/2/303
|View full text |Cite
|
Sign up to set email alerts
|

Raman solitons in transient SRS

Abstract: We report the observation of Raman solitons on numerical simulations of transient stimulated Raman scattering (TSRS) with small group velocity dispersion. The theory proceeds with the inverse scattering transform (IST) for initial-boundary value problems and it is shown that the explicit theoretical solution obtained by IST for a semi-infinite medium fits strikingly well the numerical solution for a finite medium. We understand this from the rapid decrease of the medium dynamical variable (the potential of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…where 18) and where the contour of integration has to be understood as being C − for the first vector of the product ΨR, and C + for the second. Thanks to the particular dependence in x of R(k, x) it is easy to compute Ψ x + ik[σ 3 , Ψ] and by algebraic manipulations to get…”
Section: Property P2mentioning
confidence: 99%
See 2 more Smart Citations
“…where 18) and where the contour of integration has to be understood as being C − for the first vector of the product ΨR, and C + for the second. Thanks to the particular dependence in x of R(k, x) it is easy to compute Ψ x + ik[σ 3 , Ψ] and by algebraic manipulations to get…”
Section: Property P2mentioning
confidence: 99%
“…Note that the essential property to be used is the fact that ρ(k, t) is continuous and bounded for k ∈ R at any given t. Particular attention is required when, as t evolves, a pole of ρ is "seen" to cross the real axis. It has been demonstrated in [18] that the process is continuous, or put in other words, a resonance (pole in the lower half-plane) dissapears and a pole appears while never belonging to the real axis. The same situation arises for the Schrödinger eigenvalue problem [25].…”
Section: Why It Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also achievements in the theory of solitons and SRS [6]. The numerical simulation of the transient stimulated Raman scattering based on using the inverse scattering transform technique is reported in [7]. A new type of solitons-dissipative Raman solitons-was found based on the nonlinear Ginzburg-Landau equation in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, one is based on the inverse scattering transform (IST) [11][12][13][14][15][16]. It has already been shown that vectorial SRS is solvable on the line [13] what has allowed to explain the formation of the spike of pump radiation.…”
Section: Introductionmentioning
confidence: 99%